Design for action: sviluppo tecnologico e metamorfosi delle categorie etiche - Grieco, Pasquale (Filosofia Morale/Moral Philosophy, 2024)
Design for action: technological development and metamorphosis of ethical categories This paper explores key conceptual intersections between subjectivity, technological mediation, and agency, focusing on the influence of information technologies, artificial intelligence, and digital systems on these foundational philosophical and ethical categories. The objective is to offer critical insights for rethinking these concepts in the context of the digital revolution. In light of the design turn, the study emphasizes the growing importance of embedding ethical values into artifacts and design processes, highlighting their implications for political and legislative decision-making at both national and supranational levels.